Memahami Isu Gender dan Ketidaksetaraan Gender di Indonesia Pasca Era Reformasi: Perspektif Pembangunan - Nurdin, Nurdin (Jurnal Ilmiah Global Education, 2024)
Understanding gender issues and gender inequalities in development is one of the keys to success in realizing gender equality. Indonesia after the Reformation era experienced a transformation in encouraging gender equality in various developments. The success and failure of gender development can be measured through the Human Development Index, Gender Development Index, Gender Empowerment Index, and Gender Equality and Inequality Index. This research method is qualitative through an approach to gender issues in Indonesia with in-depth analysis based on literature study data including official documents, online news, books, and previous research articles with a development perspective. The research results explain that gender equality in Indonesia have not yet shown significant progress. One of the obstacles that remain is the low level of understanding of gender issues and gaps in development among society in general and programs planners, as well as development policymakers at both the Government and Regional government levels in particular.